I hope this finds you well : a novel - Sue, Natalie (William Morrow, an imprint of HarperCollinsPublishers, 2024)
Trapped between petty revenge and a life-changing opportunity, Jolene navigates coworker drama, hidden secrets and forbidden feelings to save her job, risking exposure of an email vendetta and the walls she's built around her heart.